Transformation of technical education faculties in Turkey in the process of European Union: Faculty of applied sciences - ORAL, BÜLENT; SAĞLAM, ŞAFAK (ELSEVIER SCIENCE BV, 2010)
Countries education systems unavoidably changes to adapt themselves to innovations because of developing technology and globalization. This perspective technical education faculty position is queried which are established with the aim of educate technical teachers for vocational high schools in Turkey. Faculty of applied sciences model can replace with the technical education faculty that has completed its mission. It is possible to educate engineers with the faculty of applied sciences who has qualified, keep up the technology and has the characteristics necessary for the working life. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Technical education; engineering education; faculty of applied sciences; teacher training; vocational education